Re-crafting Architecture in Philippi + the everyday - Developing the urban potentials and sites of production in the Cape Flats - Van Breda,Travors (School of Architecture, Planning and Geomatics, 2022)
The dissertation aims to surface relevant ongoing development of the informal economies and micro-industries shaping Philippi. This provides valuable information aiding in the understanding of the existing conditions of Philippi. The focus area of the Philippi Industrial Precinct sits on the eastern periphery of Cape Town, it is a township well located in the greater city metropolitan. It is a severely under-resourced area with a rich potential for a site of production and vibrant urban culture. The scope of work aims to establish a more nuanced comprehension of informality, its connection to the wider formal networks, and what opportunity it represents to a new architectural culture. The understanding of these aspects and conditions frames a propositional question to how we as architects should make use of alternative practices, one that is ethically engaged with on the ground knowledge by supporting the initiatives of the collective majority in the production of space and future development. The program is meant stand as an infrastructure in alignment and informed by the existing practices of craftsmen, the use of new technologies (open-source architecture) provides a platform for emerging manufacturers to be educated in the form of accredited vocational training and cultural exchange. This form of architecture is viable in South Africa due to existing socio-economic condition with willing workforce seeking work opportunities and the established systems of thinking. The architectural project seeks to create micro-systems of manufacturing and designing a building as a social catalyst.